Dampak Home Industry Pengrajin Anyaman Bambu Reyeng Sebagai Produk Khas Lokal Trenggalek Dalam Meningkatkan Ekonomi Keluarga Menurut Perspektif Ekonomi Islam - Yulinda Darwiyanti (Niqosiya: Journal of Economics and Business Research, 2025)
This study aims to determine the impact of the home industry of reyeng bamboo weavers in improving the family economy in Trenggalek Regency. The focus of this study is to understand the role of home industries in meeting household needs and reviewed from an Islamic economic perspective. This study uses qualitative research methods that focus on facts occurring in the field with an inductive and descriptive or explanatory approach. Data were collected through interviews with bamboo weavers in Trenggalek Regency. The findings of this study indicate that home industries in Trenggalek Regency are able to meet family economic needs, reduce unemployment, and provide benefits. From an Islamic economic perspective, this activity does not violate Islamic principles and rules, both in terms of raw materials, production processes, and sales, except for fluctuating selling prices, and the system used is still simple and manual. The results of this study indicate that the home industry of reyeng bamboo weaving can improve the family economy in Trenggalek Regency. The success of home industries for the welfare of the community requires support from the local government in order to develop home industry businesses to improve the family economy and absorb labor.